On differentiability of solution to stochastic differential equation with fractional Brownian motion - Mishura, Yu.S.; Shevchenko, G.M. (Інститут математики НАН України, 2007)
Stochastic differential equation with pathwise integral with respect to fractional Brownian motion is considered. For solution of such equation, under different conditions, the Malliavin differentiability is proved. Under infinite differentiability and boundedness of derivatives of the cofficients it is proved that the solution is infinitely differentiable in the Malliavin sense with all derivatives bounded.